Marsupialization as conservative initial treatment for calcifying odontogenic cyst: case report (Research, Society and Development, 2022)
Introduction: The calcifying odontogenic cyst (COC) appears in the oral cavity as a slow growing swelling, usually painless, with prevalence in the anterior region of the maxilla and mandible without gender predilection, affecting an average age of 30 years. Objective: The objective of this paper is to report the importance of diagnosis with the minimally invasive surgical approach for large pathologies. Case report: A 14-year-old patient, complaining of progressive swelling on the left side of the face close to the nose, for about 01 (one) year, undergoing marsupialization and incisional biopsy as the initial surgical approach for treatment . Discussion: The case report has characteristics similar to those found in the literature on COC to date, in agreement with diagnosis, treatment and post-surgical follow-up. Conclusion: The marsupialization performed showed regression of the lesion size and formation of calcification areas in the lesion, bringing benefits to the patient. Keywords: Calcifying Odontogenic Cyst; Odontogenic Cyst; Surgical Decompression.